PENERAPAN METODE ACTIVITY BASED COSTING DALAM MENENTUKAN HARGA POKOK PRODUKSI PADA RIZQUNA JOYO CLUB KEDIRI - Kusuma, Lia Mar’atus; Subagyo, Subagyo (Universitas Nusantara PGRI Kediri, 2017)
This research is based on different views related to the activity based costing method, and conventional method in determining the cost of production of ikat woven crafts which will have an impact on the development of the company's profit. But most of the previous research views show activity-based costing methods as a more cost effective seller of sales for companies that produce heterogeneous products. The purpose of this study is to test the activity-based costing method in determining the cost of production of ikat woven crafts, and to compare the results between the method used by the company that is conventional method with the method that the researcher discuss is the activity based costing method. This study uses a quantitative descriptive approach, which is a problem-solving process done by analyzing data in the form of numbers. This study uses documentation and interview instruments. The results of this study is the acquisition of the cost of goods sold on ikat fabrics products Rp 11.401.611.2 with the calculation of conventional methods, and Rp 11.401.610.1 with activity based costing method. This shows that the cost of production reported to have excess of Rp. 1.10 from Rp 11.401.611.1. As for batik ikat batik cloth products obtained the calculation of cost of production amounted to Rp 13,490,611.14, and calculations by the method of activty based costing to produce cost of production amounted to Rp 12.973.026,61. This shows that the reported cost of goods manufactured is Rp 517,584.53 from Rp 13,490,611.14. Suggestion delivered in this research should Rizquna Joyo Club Kediri apply activity based costing method to determine cost of goods production. Because the activity-based costing method is more appropriate to be used for companies that produce products that are heterogeneous, so as to be able to assist management in making decisions on the control activities that exist during the production process that will affect the profitability of the company.